Callus formation of Coffea canephora induced with 2,4 dichlorophenoxyacetic acid and tomato extract supplements - Fahira, Nurul Rifqah; Latunra, Andi Ilham; Johannes, Eva (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2023)
Robusta coffee (Coffea canephora) is Indonesia's essential leading trade commodity. Robusta coffee is preferred for its bitter taste. However, robusta coffee productivity decreased due to bad agriculture practice. Tissue culture is an alternative to cultivation with various advantages. The plant growth regulators (PGRs) influence tissue culture’s success. Due to its stability, 2,4 dichlorophenoxyacetic acid has become a common synthetic PGRs. PGRs can be obtained from natural ingredients, such as tomatoes. This study aimed to analyze the effect of 2,4-dichlorophenoxyacetic acid and tomato extract addition and its appropriate concentration for callus induction of robusta coffee in vitro. This research was conducted at the Tissue Culture Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University. This study used a Complete Randomized Design with two factors. The first factor was the concentration of tomato extract (0%; 7.5%; 10%; and 12.5%). Meanwhile, the second factor was the concentration of 2,4 dichlorophenoxyacetic acid (0 ppm; 1 ppm; 2 ppm; and 3 ppm). Observation parameters include the percentage of callus formation, callus growing time, callus fresh weight, callus color, and callus texture. The quantitative data were analyzed by the Kruskal-Wallis test followed by the Mann-Whitney Test to compare the effect of each treatment. The results showed that among other treatment combinations, treatment with the addition of 2 ppm 2,4-D and 10% tomato extract (T2D2) and treatment with the addition of 3 ppm 2,4-D and 10% tomato extract (T2D3) had the best effect in inducing the callus of robusta coffee.